An Observational Study on Refraction, Intraocular Pressure, and Macular Thickness after Nd:YAG Laser Posterior Capsulotomy in a Tertiary Care Centre of Uttarakhand - Tarannum Shakeel; Sushobhandas Gupta; Vatsala Vats; Ashish Kakkar (TNOA Journal of Ophthalmic Science and Research, 2025)
Objective: To study the effect of neodymium: yttrium–aluminum–garnet (Nd:YAG) laser capsulotomy on the refractive status, intraocular pressure (IOP), and macular thickness (MT) in pseudophakic patients undergoing treatment for posterior capsular opacification. Material and Methods: It was a hospital-based, prospective observational study conducted on 76 pseudophakic eyes with posterior capsule opacification, where Nd:YAG laser capsulotomy was performed as a therapeutic measure. Patients underwent complete ophthalmic evaluation including best corrected visual acuity (BCVA), IOP, spherical equivalent (SE), and MT prior to laser. The same parameters were recorded at 1 h, 1 week, and 4 weeks post capsulotomy, and the findings were compared. Results: BCVA improved significantly in all eyes with capsulotomy; however, no statistically significant difference was noted in SE in all the groups. IOP showed a spike 1 h post laser, and then a decline, in eyes where less than 25 mJ laser energy was used, while it remained significantly higher when the energy required to open the capsule was more than 50 mJ. MT increased at 1 h in all eyes after laser; however, it decreased over a period of 4 weeks. For those peudophakics where more than 50 mJ energy was used, the MT, despite its decrease, still remained significantly higher than pre-laser status. Conclusion: Nd:YAG capsulotomy is an effective tool to treat posterior capsular opacification that enhances BCVA without much alteration on SE. However, the incremental effects on IOP and MT do not always call for an intervention.